Larvae of the Nearctic species of the stonefly genus Megarcys Klapálek (Plecoptera: Perlodidae) - Stewart, Kenneth W. (Illiesia, 2012)
Associated larvae of the five Nearctic species of Megarcys are comparatively described and illustrated. Four of them, Megarcys irregularis Banks, M. subtruncata Hanson, M. watertoni (Ricker), and M. yosemite (Needham & Claassen) are described in detail for the first time. Body size and setation, wingpad macroptery/brachyptery, and gill size were variable between populations of some species. Diagnostic differences were not found in late instar larvae of the five species in color and pigment patterns, mouthparts, body and appendage setation, gill size and structure, and developing male and female genitalia. The detailed descriptions and measurements help expand the generic diagnosis, show morphological differences between populations of different habitats, and provide an atlas of illustrations for larvae of the five species.
Keywords: entomology; stonefly larvae; Plecoptera; Megarcys; Nearctic